Implementation of Total Quality Management (TQM) to Improve Education Quality at MAS Darul Aitami South Aceh - Pansurna; Cut Zahri Harun; Niswanto (Hikmatuna : Journal for Integrative Islamic Studies, 2022)
The concept of Quality Management is very developed and widely applied, especially in the world of education, an educational management approach has developed, namely Total Quality Management (TQM). The aims of this study were to determine: (1) the implementation of the TQM program at MAS Darul Aitami Aceh Selatan to improve the quality of education; (2) efforts made by madrasah principals in implementing TQM; and (3) inhibiting factors in TQM implementation. Data collection techniques through: observation, interviews, and documentation studies. The research subjects included madrasah principals, educators, and education staff. Data analysis using data reduction, data presentation, and drawing conclusions. The results showed: (1) TQM implementation in improving the quality of education includes the implementation of curriculum management, teacher and staff management, student management, madrasah relationship management with the community, and madrasah climate management. (2) Efforts made include: having a strong commitment and will and continuing to strive for quality improvement and working based on quality, increasing teacher professionalism and competence, compiling and planning madrasah programs, empowering madrasah resources to the maximum, providing educational facilities and infrastructure , improve teacher welfare, conduct guidance and enrichment programs for student learning, develop religious culture in madrasah, establish cooperation with madrasah committees.